Gendered Language and Gendered Violence - Lewis Davis; Astghik Mavisakalyan; Clas Weber (Global Labor Organization (GLO), 2022)
This study establishes the influence of sex-based grammatical gender on gendered violence. We demonstrate a statistically significant relationship between gendered language and the incidence of intimate partner violence in a cross-section of countries. Motivated by this evidence, we conduct an individual-level analysis exploiting the differences in the language structures spoken by individuals with a shared religious and ethnic background residing in the same country. We show that speaking a gendered language is associated with the belief that intimate partner violence is justifiable. Our results are consistent with the theoretical possibility that gendered language activates gender schemata in the minds of speakers, increasing the salience of gender distinctions and existing gender norms which legitimize gendered violence.
Keywords: J12; Z13; D83; 330; gender; language; cultural norms; intimate partner violence